Pre-Service English Teacher’s Perception and Understanding Toward TPACK Framework During Microteaching Course - Mariette, Komang Shinta (English Education Department STKIP Agama Hindu Singaraja, 2022)
TPACK become a euphoria in Indonesia. The aim of this study was to investigate the pre-service teachers’ perceptions and understanding of technological pedagogical content and knowledge during their microteaching class in EFL context. This study was framed within the descriptive qualitative design. The study employed a TPACK questionnaire and an interview guide. The study was distributed to 100 pre-service English teachers at English Language Education. The data were collected through online survey and were analyzed using descriptive analysis. The result shows pre-service teachers have very positive perceptions towards TPACK. It was found that the pre-service teachers also already have a good knowledge in implementing TPACK. However, there are some aspects, like class room management that need to be improved.